Frequency and severity of potential drug interactions in a cohort of HIV-infected patients Identified through a Multidisciplinary team. Issue 1 (2nd January 2018) - Molas, E.; Luque, S.; Retamero, A.; Echeverría-Esnal, D.; Guelar, A.; Montero, M.; Guerri, R.; Sorli, L.; Lerma, E.; Villar, J.; Knobel, H.
Abstract : Objectives: Interactions between antiretroviral treatment (ART) and comedications are a concern in HIV-infected patients. This study aimed to determine the frequency and severity of potential drug–drug interactions (PDDIs) with ART in our setting. Methods: Observational study by a multidisciplinary team in 1259 consecutive HIV patients (March 2015-September 2016). Data on demographics, toxic habits, comorbidities, and current ART were collected. A structured questionnaire recorded concomitant medications (including occasional and over-the-counter drugs). PDDIs were classified into four categories: (1) no interactions, (2) mild (clinically non-significant), (3) moderate (requiring close monitoring or drug modification/dose adjustment), and (4) severe (contraindicated). Statistical analysis: chi-square test, logistic regression analysis. Results: In total, 881 (70%) patients took comedication, and 563 (44.7%) had ≥ PDDI. Forty-one comedicated patients (4.6%) had severe and 522 (59.2%) moderate PDDIs. Moderate PDDIs mainly involved cardiovascular (53.8%) and central nervous system (40.2%) drugs. Independent risk factors for PDDIs were ART containing a boosted protease inhibitor (odds ratio [OR]=9.11, 95% confidence interval [CI] 5.15–16.11; p  = 0.0001) and/or non-nucleoside reverse transcriptase (NNRTI) (OR = 4.34, 95%CI 2.49–7.55; p  = 0.0001), HCV co-infection (OR = 3.26, 95%CI 2.15–4.93; p  = 0.0001), and use of two or more comedications (OR = 3.36, 95%CI 2.27–4.97; p  = 0.0001). Adherence and effectiveness of ART were similar in patients with and without PDDIs. The team made 133 recommendations related to comedications (drug change or dose adjustment) or ART (drug switch or change in administration schedule). Conclusions: Systematic evaluation detected a significant percentage of PDDIs requiring an intervention in HIV patients on ART. Monitoring and advice about drug–drug interactions should be part of routine practice.